Effectiveness of Project Based Learning (PjBL) to Improve Natural Science Learning Outcomes Of Grade IV Students - Turyati, Turyati; Hartati, Sri; Nugraheni, Nursiwi (Elementary School Teacher, 2019)
This research aimed to determine the effectiveness of Project Based Learning (PjBL) with the model in control class towards science learning outcomes on Elementary School fourth grade students in Cluster Ikan Lodan Semarang. The research is a quasi-experimental design with pretest posttest nonequivalen control group design. The population is all students of SDN in Cluster Ikan Lodan. Sampling technique is purposive sampling. The Data collection techniques are observation, testing and documentation. The results showed that thitung > t table is 3,22> 2,00 it means ho rejected and ha accepted. The conclusions of this study is the experimental class that implements the Project Based Learning (PjBL) model is more effective than applying the model on class control with Contextual Teaching and Learning (CTL) on material changes the physical environment in the fourth grade students of SDN in cluster Ikan Lodan North Semarang districts.